A Conceptualization of the Urban Food-Energy-Water Nexus Sustainability Paradigm: Modeling From Theory to Practice - Schulterbrandt Gragg, Richard; Anandhi, Aavudai; Jiru, Mintesinot; Usher, Kareem M. (Frontiers in Environmental Science, 2018)
Food is the essential foundation for sustainable and healthy communities. Increasing population and urbanization, limited resources, and complexities of interactions necessitate a comprehensive and in-depth understanding of the dynamics of the global trend of urbanization. The key objective of this paper is to characterize new environmental, social and economic perspectives and practices that are responsive to the rapidly urbanizing agricultural food system. We used the sustainability paradigm in the context of environmental, social, and economic sustainability to outline the three transitioning states and perspectives (unconnected/silos; interconnected/linkages; and interdependent/nested/systems) for urban agricultural food systems. We sought to ferret out the key driver/response variables and their cross-scale interactions in the urbanizing food-energy-water nexus. We used a five-step qualitative analytical method to develop a cursory conceptual model to capture the interacting variables and their responses. The complexity in the driver/response variables and their cross-scale interactions were identified. These variables were combined with outside dimensions (e.g., innovation, stakeholders, urbanization) for selected scenarios and deconstructed using spider web and causal loop models. The urbanizing socio-ecological systems, across various spatial (local to global) and temporal scales (days to millennium) as well as smaller temporal scales (days to decades) are described. The iterative multidimensionality of the model makes clear new ways of seeing sustainability issues and opens opportunities for policy solutions, resources and stakeholders to be brought to bear on the food-energy-water nexus.